2018
DOI: 10.1108/sajbs-07-2018-0077
|View full text |Cite
|
Sign up to set email alerts
|

Do the changes in macroeconomic variables have a symmetric or asymmetric effect on stock prices? Evidence from Pakistan

Abstract: Purpose The purpose of this paper is to examine whether macroeconomic variables have a symmetric or asymmetric effect on stock prices (SP) of Karachi Stock Exchange 100 index in the context of Pakistan. It also examines whether the asymmetric impact of macroeconomic variables on SP has been affected by tail events such as the global financial crisis. Design/methodology/approach This study uses linear and nonlinear autoregressive distributed lag models for the full sample period as well as in pre- and post-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 46 publications
2
30
0
3
Order By: Relevance
“…We have discovered a small number of developed and developing countries with a positive relationship (See Table 4). Fama (1981), Mukherjee and Naka (1995) and Ho (2017) found a negative relation with stock returns while Barakat et al (2015) and Chang and Rajput (2018) found a positive relation in Egyptian stock and Karachi stock, respectively. They clarified that an increase in inflation as a result of increased demand for current supply raises firms' earnings and dividends.…”
Section: Findings and Discussionmentioning
confidence: 97%
“…We have discovered a small number of developed and developing countries with a positive relationship (See Table 4). Fama (1981), Mukherjee and Naka (1995) and Ho (2017) found a negative relation with stock returns while Barakat et al (2015) and Chang and Rajput (2018) found a positive relation in Egyptian stock and Karachi stock, respectively. They clarified that an increase in inflation as a result of increased demand for current supply raises firms' earnings and dividends.…”
Section: Findings and Discussionmentioning
confidence: 97%
“…() that is nonlinear Autoregressive Distributed Lag (NARDL) which is nascent econometric techniques that determine the asymmetric effect of exchange rate changes on the stock prices both in the short run and in the long run. This technique can be used in the mixture of the order of integration (I(0) & I(1)) just avoiding an order of integration as I(2) for the variables under study (Anjum, Ghumro, & Husain, ; Chang & Rajput, ; Chang, Rajput, & Ghumro, ).…”
Section: Methodsmentioning
confidence: 99%
“…Fratzscher () also indicate that the asymmetric effect of financial and economic variables is affected by the global financial crisis. Chang and Rajput () conduct study in the context of Pakistan for examining the asymmetric effect of macroeconomic variables on stock prices. Their findings conclude that the asymmetric relationship between macroeconomic variables and stock prices changes as a result of the financial crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study done by Sui and Sun (2016) observed that trade flow model better explains the exchange rate transmission to BRICS stock market. Recent study done by Chang and Rajput (2018) by which asymmetric effects of different macroeconomic variables such as consumer price inflation, interest rate, industrial production and REER were studied on stock prices. Bahmani-Oskooee and Kanitpong (2017) found that the presence of asymmetry in real exchange rates on the trade balance, that is, the effect of appreciation or depreciation of the local currencies of nations have a different impact on their imports and exports.…”
Section: Literature Reviewmentioning
confidence: 99%